The soul of Mozambique: an autoethnographic and performance-based study on the correlation of glabalisation, Chopi people migrations and the reinterpretation of timbila music in Mozambique - Bande Júnior, Venâncio (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
This is an autoethnographic and performance-based study on the correlation between indigenous and modern cultures. It discusses the influence of globalisation, modernity, and of the Chopi people migrations to Maputo, the main city of Mozambique and to gold and platinum mines in South Africa, on timbila music. Timbila is both the name of a musical instrument (xylophone) and of a cultural manifestation, practiced by the Chopi people from Mozambique. It is one of the most documented music and dance cultures in Mozambique and was proclaimed as a masterpiece of the oral and immaterial heritage of humanity by UNESCO in 2005. The oldest references by Father Andre Fernandes date from the 16th century. However, the most well-known timbila sources were written and recorded by Hugh Tracey, the founder of the International Library of African Music (ILAM), from 1940s. All these sources were based on traditional timbila music. None refers to contemporary timbila music, which is a mixture of timbila with Western musical instruments. The research is thus based on both historical and is new research to understand the role of the phenomena mentioned above to the reinterpretation of timbila music over the time. Performance based and autoethnography methods were selected because of my role as a pedagogue of the music and culture of timbila, allowing me to express my knowledge on this cultural expression. Literature review and interviews are the two procedures of data collecting employed to get an understanding of the research methods; the phenomena of modernity, globalisation and of the Chopis migration for the searching of better living conditions in Maputo and South Africa; and the approaches of different scholars who have written about timbila. The use of these methods and methodologies, allowed me to conclude that, Chopis migrations, modernity and globalisation has allowed the emergence of a modern version of timbila music; internationalisation and dissemination of this musical expression; and contributes to the extinction of traditional timbila orchestras in Zavala. Despite considerable studies on timbila music and culture, this thesis is important and pioneering, from the perspective of studying the influence of Chopis migrations, globalisation and modernity on timbila and is one of the few sources that approach the contemporary timbila music.
Keywords: Timbila; Chopi (African people) -- Mozambique; Music festivals -- Mozambique; Traditional knowledge; Music and globalization; Modernity; Traditional folk music